The urbanization process in the Third World explorations in search of a theory - McGee, T.G. (London G. Bell and Sons, Ltd., 1971)
A collection of essays whose theme is one of growing disillusionment with the application of urban theories developed in the West to urbanization process in the third world... The first section attempts to show the limitations of the 'similar path' theories and to put forth alternative theoretical models for analysis of urbanization in the third world. The second section is based on the author's fieldwork in Southeast Asia and by actual examples he illustrates the inadequacy of the Western - based theoretical model of the urbanization process.
pt. 1. Theoretical Explorations -- The Urbanization Process: Western Theory and Third World Reality -- The Rural-Urban Continuum Debate: The Preindustrial City and Rural-Urban Migration -- Revolutionary Change and the Third World City: A Theory of Urban Involution -- P.2. The Test of Reality -- An Aspect of Urbanization in Southeast Asia: The Process of Cityward Migration -- The Cultural Role of Cities: A Case Study of Kuala Lumpur -- Appendix. Key to the location of census divisions in Kuala Lumpur -- Malays in Kuala Lumpur City: An Investigation of one Aspect of the Process of Urbanization-Occupational Mobility -- Appendix. Occupational Classification adopted for study of Malay Occupational Mobility in Kuala Lumpur.
Includes bibliographical references.
Keywords: Urbanization -- Developing countries